Light‐Controlled Orthogonal Covalent Bond Formation at Two Different Wavelengths. Issue 22 (24th April 2019) - Menzel, Jan P.; Feist, Florian; Tuten, Bryan; Weil, Tanja; Blinco, James P.; Barner‐Kowollik, Christopher
Abstract: We report light‐induced reactions in a two‐chromophore system capable of sequence‐independent λ ‐orthogonal reactivity relying solely on the choice of wavelength and solvent. In a solution of water and acetonitrile, LED irradiation at λ max =285 nm leads to full conversion of 2, 5‐diphenyltetrazoles with N ‐ethylmaleimide to the pyrazoline ligation products. Simultaneously present o ‐methylbenzaldehyde thioethers are retained. Conversely, LED irradiation at λ max =382 nm is used to induce ligation of the o ‐methylbenzaldehydes in acetonitrile with N ‐ethylmaleimide via o ‐quinodimethanes, while 2, 5‐diphenyltetrazoles also present are retained. This unprecedented photochemical selectivity is achieved through control of the number and wavelength of incident photons as well as favorable optical properties and quantum yields of the reactants in their environment. Abstract : Light and water define opposite outcomes : Two colors of light are used to selectively activate one substrate each in a two‐chromophore system for light‐induced ligation. Control over which of the two ligation reactions takes place is achieved through the selected wavelength of the irradiation and the water content of the solution.